Situasi Dan Gambaran Ketahanan Pangan di Provinsi Banten Berdasarkan Peta Fsva Dan Indikator Ketahanan Pangan - Yeni Budiawati; Ronnie S Natawidjaja (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to describe the situation and condition of food security in Banten Province by comparing food security based on the FSVA map of Banten Province (2018) which uses 9 indicators with research by Deby Eryani Setiawan et al (2017) which uses 6 indicators, then also compared with data- associated secondary data. The results show that even though the FSVA map Banten Province is in a food-resistant condition (Priority 5), if viewed from each indicator, there are still some areas or households that are still vulnerable. The order of 9 indicators from the most vulnerable to resistant in Banten Province is the percentage of stunted children under five, the percentage of malnourished children under 15 years of age, the average length of school for girls over 15 years, the percentage of households without access to clean water, the proportion of expenditure on food to total expenditure, life expectancy, percentage of households without access to electricity, percentage of population below the poverty line, and the best indicator is the ratio of population per health worker. Based on the Food Security Index for each Regency / City in Banten Province, it shows that Serang City has the lowest Food Security Index (IKP) value compared to other districts / cities in Banten Province and is in the low category of food insecure areas.